Time-motion analysis of olympic wrestlers - Drider, A.; Vitel, V.; Schortgen, A.; Moussa, I.; Leroy, P.; Sauliere, G.; Goyallon, T.; Fruchard, B.; Vazeilles, P.; Reveret, L.; Toussaint, J. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Training scheduling cannot be separated from what happens in competition. Understanding the demands of competition allows training content to be better adapted and individualised [1]. In this sense, computer is a great tool to achieve this. It allows us to collect information as faithfully as possible while being non-intrusive [2]. The objective of this work is to determine the tactical demands by weight category and then to model the duration of the fight according to the style of wrestling.